The sulfur budget and sulfur isotopic composition of Martian regolith breccia NWA 7533. (8th September 2020) - Lorand, Jean‐Pierre; Labidi, Jabrane; Rollion‐Bard, Claire; Thomassot, Emilie; Bellucci, Jeremy J.; Whitehouse, Martin; Nemchin, Alexander; Humayun, Munir; Farquhar, James; Hewins, Roger H.; Zanda, Brigitte; Pont, Sylvain
Abstract: The sulfur isotope budget of Martian regolith breccia (NWA 7533) has been addressed from conventional fluorination bulk rock analyses and ion microprobe in situ analyses. The bulk rock analyses yield 865 ± 50 ppm S in agreement with LA‐ICP‐MS analyses. These new data support previous estimates of 80% S loss resulting from terrestrial weathering of NWA 7533 pyrite. Pyrite is by far the major S host. Apatite and Fe oxyhydroxides are negligible S carriers, as are the few tiny igneous pyrrhotite–pentlandite sulfide grains included in lithic clasts so far identified. A small nonzero Δ 33 S (−0.029 ± 0.010‰) signal is clearly resolved at the 2σ level in the bulk rock analyses, coupled with negative CDT‐normalized δ 34 S (−2.54 ± 0.10‰), and near‐zero Δ 36 S (0.002 ± 0.09‰). In situ analyses also yield negative Δ 33 S values (−0.05 to −0.30‰) with only a few positive Δ 33 S up to +0.38‰. The slight discrepancy compared to the bulk rock results is attributed to a possible sampling bias. The occurrence of mass‐independent fractionation (MIF) supports a model of NWA 7533 pyrite formation from surface sulfur that experienced photochemical reaction(s). The driving force that recycled crustal S in NWA 7533 lithologies—magmatic intrusions or impact‐induced heat—is presently unclear. However, in situ analyses also gave negative δ 34 S values (+1 to −5.8‰). Such negative values in the hydrothermal setting of NWA 7533 are reflective of hydrothermal sulfides precipitated from H2 S/HS ‐ aqueous fluid produced via open‐system thermochemical reduction of sulfates at high temperatures (>300 °C).